Forecasting the effects of accelerated sea‐level rise on tidal marsh ecosystem services. Issue 2 (24th June 2008) - Craft, Christopher; Clough, Jonathan; Ehman, Jeff; Joye, Samantha; Park, Richard; Pennings, Steve; Guo, Hongyu; Machmuller, Megan
Abstract : We used field and laboratory measurements, geographic information systems, and simulation modeling to investigate the potential effects of accelerated sea‐level rise on tidal marsh area and delivery of ecosystem services along the Georgia coast. Model simulations using the Intergovernmental Panel on Climate Change (IPCC) mean and maximum estimates of sea‐level rise for the year 2100 suggest that salt marshes will decline in area by 20% and 45%, respectively. The area of tidal freshwater marshes will increase by 2% under the IPCC mean scenario, but will decline by 39% under the maximum scenario. Delivery of ecosystem services associated with productivity (macrophyte biomass) and waste treatment (nitrogen accumulation in soil, potential denitrification) will also decline. Our findings suggest that tidal marshes at the lower and upper salinity ranges, and their attendant delivery of ecosystem services, will be most affected by accelerated sealevel rise, unless geomorphic conditions (ie gradual increase in elevation) enable tidal freshwater marshes to migrate inland, or vertical accretion of salt marshes to increase, to compensate for accelerated sea‐level rise.